2020
DOI: 10.1021/acschemneuro.0c00161
|View full text |Cite
|
Sign up to set email alerts
|

First Radiolabeling of a Ganglioside with a Positron Emitting Radionuclide: In Vivo PET Demonstrates Low Exposure of Radiofluorinated GM1 in Non-human Primate Brain

Abstract: Gangliosides are biologically important glycolipids widely distributed in vertebrate cells. An important member of the ganglioside family is the monosialylganglioside GM1, which has been suggested as a potential therapeutic for Parkinson’s disease. In the current study, a late-stage radiofluorination protocol was developed, in which fluorine-18 was introduced by substitution of a terminal tosyl group in the fatty acid backbone of GM1. The radiofluorination procedure was remarkably simple and furnished the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Recently, fluorinated [ 18 F]F-GM1 was used to assess brain penetration of the ganglioside after intravenous administration in cynomolgus monkeys, by positron emission tomography (PET). This study demonstrated that only 0.4% of the injected dose entered the brain, without any increase over a period of 4 h (Revunov et al, 2020). Thus, poor brain penetration of peripherally injected GM1 likely explains the negative or modest results obtained in past clinical trials.…”
Section: Clinical Applications Of Gm1mentioning
confidence: 70%
See 1 more Smart Citation
“…Recently, fluorinated [ 18 F]F-GM1 was used to assess brain penetration of the ganglioside after intravenous administration in cynomolgus monkeys, by positron emission tomography (PET). This study demonstrated that only 0.4% of the injected dose entered the brain, without any increase over a period of 4 h (Revunov et al, 2020). Thus, poor brain penetration of peripherally injected GM1 likely explains the negative or modest results obtained in past clinical trials.…”
Section: Clinical Applications Of Gm1mentioning
confidence: 70%
“…Overall, the demonstrated safety profile of GM1 and the compelling evidence of its disease-modifying effects in HD (Di Pardo et al, 2012;Alpaugh et al, 2017) and in PD (Schneider et al, 2019) warrant further clinical investigation in patients. The development of strategies to overcome issues with drug delivery across the blood-brain barrier (BBB) (Revunov et al, 2020) will be crucial to this endeavor, even for the treatment of neurodegenerative/trauma-related conditions where the BBB might be partially compromised. Recent studies suggested that the pentasaccharide component of the GM1 molecule, which can reproduce the ganglioside effects on TrkA receptor activation and signaling (Chiricozzi et al, 2017;Di Biase et al, 2020a), can cross an in vitro model of BBB through a paracellular route (Di Biase et al, 2020b).…”
Section: Additional Considerations and Conclusionmentioning
confidence: 99%
“…Past studies showed that a very scant quantity of GM1 intraperitoneally injected into mice reached the brain, a part of which was found in the brain blood vessels [92]. The reduced capability of GM1 to cross the BBB has been recently confirmed in primates subjected to PET analysis after intravenous injection of fluorinated [ 18 F]GM1 [93]. This study demonstrated that only the 0.4 % of injected GM1 entered the brain.…”
Section: Oligogm1 As a Drug For Neurodegenerative Diseasesmentioning
confidence: 51%
“…Selective uptake in E. coli over mutant strain and mammalian cells. 139 49 6′′-[ 18 F]-Fluoromaltriose Pathogenic bacteria NucleophilicNude mice infected with Escherichia coli Tracer was accumulated in infected muscle 3.5 fold in comparison to un-infected contralateral muscle 140 50 [ 18 F]AAX21 Pathogenic bacteria Nucleophilic followed by click chemistryBlood serum (human)Stable in human blood serum (>120 min) 142 51 [ 18 F]-GM1 Neurodegenerative disease NucleophilicCynomolgus monkey (Non-human primate brain)SUV (brain) > 0.4 Brain: blood ratio = 0.03Low uptake in the brain compared with previous studies. High uptake in the heart could lead to complications with vascular insulin resistance and heart failure. 146 57 α-5′-[ 18 F]-FAZA Hypoxia NucleophilicHuman (high-grade glioblastoma)Tumour: brain ratio = 5.3Average over 7 patients. High ratio aided by lack of tracer accumulation in normal brain tissue. 164 58 β-5′-[ 18 F]-FAZR Hypoxia NucleophilicHCT 116 colorectal carcinoma cellsPoor interaction with five hNTs suggests β-5′-[ 18 F]-FAZR is not transported into human cells efficiently. 165 59 β-6′-[ 18 F]-FAZAL Hypoxia NucleophilicEMT6 tumour bearing NMRI- Foxn1 miceTumour: muscle ratio (120 min) = 2.13Ratio from hypoxic conditions in comparison to normoxic at 1.22. 166 60 β-2′-[ 18 F]-FAZA Hypoxia Nucleophilic 167 61 β-3′-[ 18 F]-FAZL Hypoxia Nucleophilic 167 62 [ 18 F]-FDG-2-NIm Hypoxia NucleophilicWistar rats injected with Walker 256 rat mammary carcinoma cellsUptake in tumour = 0.43 ± 0.09% ID per gDoes not a...…”
Section: Appendix Imentioning
confidence: 99%